On the $h$-vectors of Cohen-Macaulay Flag Complexes - Constantinescu, Alexandru; Varbaro, Matteo (MATHEMATICA SCANDINAVICA, 2013)
Starting from an unpublished conjecture of Kalai and from a conjecture of Eisenbud, Green and Harris, we study several problems relating $h$-vectors of Cohen-Macaulay, flag simplicial complexes and face vectors of simplicial complexes.